Implementasi Microsoft Acces Dalam Sistem Informasi Manajemen Usaha Wadah Laundry - Nayla Putri Syadiva; Mutia Salsabila; Wulan Juani Salsa Billa; Nur Asy Syifa'; Angga Kusumah (LPPM Universitas Bina Sarana Informatika, 2025)
Wadah Laundry is a business that records transactions manually without a structured bookkeeping system. This leads to difficulties in monitoring operational income and expenses, making it unclear whether the business is generating profit or loss. Therefore, this study aims to develop an information system based on Microsoft Access to facilitate transaction recording, monitor financial flows, and calculate profit or loss more accurately. This research employs a field study method by collecting data directly through observations and interviews related to the business’s operational processes. The developed system includes key features such as customer transaction recording, customer data management, data storage, editing, deletion, and report generation as needed. The implementation results show that this system can help process data more effectively, making transaction recording more organized and accurate. Thus, the developed application is expected to support Wadah Laundry’s operations by improving business management efficiency.